International Classification of Diseases, Ninth Revision (ICD-9) Diagnosis Codes Can Identify Cerebral Venous Thrombosis in Hospitalized Adults. (October 2016) - Liberman, Ava L.; Kamel, Hooman; Mullen, Michael T.; Messé, Steven R.
Background: Cerebral venous thrombosis (CVT) is a relatively rare and understudied disease. We sought to determine the accuracy of International Classification of Diseases, Ninth Revision ( ICD-9 ) diagnosis codes to identify CVT. Methods: Retrospective chart review using the electronic medical record (EMR) to identify all patients discharged with CVT following admission or emergency department visit from May 1, 2010 to May 1, 2015 at our center. Results: We identified 111 patients with an ICD-9 discharge diagnosis code of 325.0 (cerebral sinovenous thrombosis, excluding nonpyogenic cases and cases associated with pregnancy and the puerperium), 437.6 (CVT of nonpyogenic origin), or 671.5 (CVT complicating pregnancy, childbirth, or the puerperium) in any position. Of these 111 patients, 84 (75.7%) had confirmed CVT after EMR review. Searching outpatient and radiology records, we found an additional 24 patients with CVT who were not identified via query of ICD-9 discharge diagnosis codes. The ICD-9 codes 325.0, 437.6, or 671.5 in any position had a combined sensitivity of 77.8% and specificity of 92.7%; in the primary position, they had a sensitivity of 28.7% and specificity of 98.3%. Conclusion: The ICD-9 codes 325.0, 437.6, and 671.5 can be used to identify CVT with acceptable sensitivity and specificity.